Orthodox churches in Ukraine before and after the Euromaidan revolution - Mudrov, Sergei A. (Journal of the Belarusian State University. Sociology, 2020)
I discuss the religious life in Ukraine before and after the 2014 «revolution of dignity». The main focus of the article is on the Orthodox сhurches, as the most numerous and influential in Ukraine. I argue that since 2014 the pressure on the Ukrainian Orthodox Church (Moscow Patriarchate) has intensified substantially, with a purpose of creating from this сhurch an image of the «radical other». The pressure was going along several lines: mass-media discussions, actions of authorities and the attempts to make changes in the relevant legislation. At the same time, the Church of Kiev Patriarchate and the Ukrainian Autocephalous Orthodox Church were receiving more support. However, the Ukrainian Orthodox Church (Moscow Patriarchate) has kept its status of the most numerous denomination, holding its firm presence in most Ukrainian regions. The attempts to marginalize this сhurch have further divided Ukrainian society, blurring the prospects for reconciliation.
Keywords: Orthodox сhurches; religion; Moscow Patriarchate; Kiev Patriarchate; autocephaly; Ukraine